Dofetilide effect on human atrial action potential under normal and atrial fibrillation conditions. In silico study (2017)
Atrial fibrillation is the most common sustained cardiac arrhythmia. Dofetilide is an antiarrhythmic drug for the treatment of chronic AF that specifically blocks the rapid component of the delayed rectifier potassium current IKr. Dofetilide prolongs the action potential duration and QT interval in a concentration-dependent fashion, therefore, the risk of QT prolongation is dose related. It is important to study the electrophysiological effects of dofetilide at different concentrations in human atrial cells. For this, we simulated the effects of dofetilide on human atrial cell and studied its effect on atrial action potential under normal conditions and during cAF. We developed a model of dofetilide effects on IKrand IKACh. Our results show that dofetilide blocks both currents in a fraction greater as the concentration increases, which results in an action potential duration lengthening. To our knowledge, this is the first work that has developed mathematical models of dofetilide effects on IKrand IKAChcurrents to study its effect on human atrial action potential. © Springer Nature Singapore Pte Ltd. 2017.